Enhancing Early Childhood English Vocabulary: Teachers’ Perspectives on Optimizing the Duolingo Application - Warmansyah, Jhoni; Puja Diandra; Enji Novita Sari; Adam Mudinillah; Suswati Hendriani; Mazlina Che Mustafa (Journal of English Education and Teaching, 2024)
Currently in Indonesia, a substantial number of young children lack proficiency in and awareness of English vocabulary, a crucial international language. This study aims to explore the potential of Duolingo application usage in improving English vocabulary among young children, specifically from the perspective of teachers. Employing a quantitative descriptive research method, data were gathered through questionnaire surveys. The results indicate that the utilization of the Duolingo application by teachers contributes positively to the learning environment, resulting in noticeable improvements in English vocabulary among early childhood learners. The children demonstrated enhanced vocabulary skills after using the application over a specific duration. However, the study also highlights that the Duolingo application should not be relied upon as the sole source for English language learning in early childhood education. Its usage needs to be integrated into structured and teacher-directed learning approaches. Effective management of the application is crucial to maximize its benefits for young learners. This research serves as a benchmark for the development of similar applications aiming to enhance English vocabulary for early childhood education, emphasizing the importance of combining digital tools with structured pedagogical methods.